2023
DOI: 10.3390/ijms24098394
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Photosynthesis Characteristics and Chlorophyll Metabolism in Leaves of Citrus Cultivar (Harumi) with Varying Degrees of Chlorosis

Bo Xiong,
Ling Li,
Qin Li
et al.

Abstract: In autumn and spring, citrus leaves with a Ponkan (Citrus reticulata Blanco cv. Ponkan) genetic background (Harumi, Daya, etc.) are prone to abnormal physiological chlorosis. The effects of different degrees of chlorosis (normal, mild, moderate and severe) on photosynthesis and the chlorophyll metabolism of leaves of Citrus cultivar (Harumi) were studied via field experiment. Compared with severe chlorotic leaves, the results showed that chlorosis could break leaf metabolism balance, including reduced chloroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Additionally, decreased chlorophyll content may be associated with decreased photosynthetic enzymes . In contrast, the results from phase II, where the hydrogel was employed in drought conditions, showed increased chlorophyll concentration compared to the control phase I.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, decreased chlorophyll content may be associated with decreased photosynthetic enzymes . In contrast, the results from phase II, where the hydrogel was employed in drought conditions, showed increased chlorophyll concentration compared to the control phase I.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, decreased chlorophyll content may be associated with decreased photosynthetic enzymes. 40 In contrast, the results from phase II, where the hydrogel was employed in drought conditions, showed increased chlorophyll concentration compared to the control phase I. This indicates that the hydrogel application can help mitigate the negative impact of drought on the chlorophyll content of sunflower plants.…”
Section: Morphological Characters In Response To Either Stress Only O...mentioning
confidence: 92%
“…On the other hand, interspecific relationships based on complementary effects are largely influenced by N availability [84]. Yao et al reported that leguminous plants transfer N to eucalyptus trees through root contact, as shown by the 15 N isotope labeling method [35,54]. This phenomenon has been observed in mixed plant species such as wheat and faba bean [85], maize and soybean [86], and Acacia mangium and Eucalyptus [55].…”
Section: Competition For N Promotes the Growth Of E Urophylla × E Gra...mentioning
confidence: 99%
“…Leaf tissue density (LTD) and leaf dry matter content Plants 2024, 13, 988 2 of 21 (LDMC) are used to estimate the compactness level and extent of leaf tissue growth, which may be related to plant responses to soil nutrient resources [6,12]. Regarding output, the net photosynthetic rate (Pn) is a decisive indicator of photosynthetic efficiency in leaves and is influenced by stomatal conductance (gs), transpiration rate (Tr), and intercellular carbon dioxide concentration (Ci) [13,14], while chlorophyll content (Chl) determines the flux size of photons received in leaves [15]. In addition, Rubisco carboxylation efficiency (CE) reflects the carboxylation efficiency of the key rate-limiting enzyme of photosynthesis [16], and leaf water-use efficiency (WUE) reflects the water use by the leaves and is closely related to the photosynthetic process [17].…”
Section: Introductionmentioning
confidence: 99%
“…Phvul.004G031900 and Phvul.004G032000 (at 3,910,100-3,975,292 bp) were associated with chlorosis and variation in maturity caused by a deletion in stop codon [60] and they were a candidate for C* pod interior and exterior in G19833 (the equivalent being Pv5-593.04G036100 in 5-593) (Table S1). In chlorotic tissues, as photosynthesis and the amount of chlorophyll decreases, the decrease in chlorophyll accelerates, and a color change occurs in the tissues by affecting various pigment syntheses [61].…”
Section: Candidate Genes From Other Studiesmentioning
confidence: 99%